Polymorphism of the oestrogen receptor (ESR) gene in some pig breeds reared in Vietnam - Thúy, Lê Thị; Minh, Lưu Quang; Thủy, Trần Thu; Bình, Nguyễn Trọng; Lân, Phạm Doãn; Vang, Nguyễn Đăng (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 45-50, 2005